Radiance: transaction level pricing in the Indian fireworks industry. Issue 3 (11th August 2014) - Pandey, Neeraj; Singh, Gaganpreet
Abstract : Subject area: – Pricing, Marketing Management, Strategic Marketing . Study level/applicability: – The case can be used for pricing course besides Marketing Management and Strategic Management course to MBA students and/or for Management Development Programmes. Case overview: – ABC Fireworks Private Limited, located in Saharanpur, was into business of manufacturing fireworks under the brand name of Radiance. The owner Mr Sudhir Kapoor was satisfied with the present revenue growth and profit margin except that the cash flow was quite intermittent. The consumption pattern of Indian fireworks industry was highly skewed. Approximately 90 per cent of the entire year manufactured stock had retail market of just 5 days ahead of Diwali festival. To cater to this massive demand, the production was carried out for the whole year. Mr Kapoor was planning to restructure pricing policy so as to have regular cash flow throughout the year. To meet this objective, he was considering price promotion strategy as a preferred option which would enable his marketing team to offer specific discounts to stockists using time slab mechanism. The fireworks industry had four channel distribution processes. The product line was broadly divided into three categories, namely, sound, aerial shots and sparkles. The organization was not into manufacturing of aerial shots product category but was planning to make a foray into it. The case provides interesting insights into pricing dynamics prevalent in the Indian fireworks industry. It includes first-hand information about fireworks price, cost break-up and profit distribution among various members of the industry's value chain. Expected learning outcomes: – The case enables students to learn the concept and application of pricing, price-based promotion, discounts and price waterfall analysis in the firework industry. Supplementary materials: – Teaching Notes are available for educators only. Please contact your library to gain login details or emailsupport@emeraldinsight.com to request teaching notes.